The analysis of incidence of risk factors of neoplastic diseases among patients with a diagnosed neoplastic disease - Lewandowska, Anna; Kostkiewicz, Marta; Lewandowski, Tomasz; Laskowska, Barbara (Journal of Education, Health and Sport, 2017)
Introduction: Risk of neoplastic diseases in the whole world’s population has been increasing regularly. Thanks to the GLOBACAN data base operating under the auspices of the International Union Against Cancer it has been reported that up to 2002 10,900,000 of new cases of cancer were diagnosed and 6,700 deaths were reported. According to the World Health Organization, in 2020 we may expect about 10 million deaths, including 7-8 millions in the developing countries, while this number in the developed countries will not change and will be 2-3 million. The world’s most frequently occurring tumour is lung cancer. It accounts for 12.4% of all tumours diagnosed. According to the epidemiological research, the basic factors responsible for cancer development among people are those environmental factors that result from humans’ behaviour. Objective: The objective is to analyze the occurrence of risk factors of a neoplastic disease among patients with a diagnosed oncological disease. Material and methods: The research involved 500 patients of the oncology department. Women accounted for more than a half of all patients, namely 58%, while men 42%. In order to obtain the research material, a standardized questionnaire has been applied, including interview and physical examination, enabling assessment and analysis of occurrence of cancer risk factors. Results: The most frequently diagnosed tumour among women is breast cancer (20%), while among men the most frequently occurring is prostate cancer (10%). 20% of women and 10% of men lived near high-voltage line. 11% of women were active smokers while 6% passive smokers. When it comes to men, 18% were active smokers, while 5% passive smokers. Conclusions: The most frequent cancer among women is breast cancer, while among men prostate cancer. Smoking does not have a significant influence on cancer development in women, however, it has a significant influence on cancer development in men. Overweight and obesity have a significant influence on cancer development in women, while they have insignificant influence on cancer development in men.